2022
DOI: 10.1021/acsami.1c18695
|View full text |Cite
|
Sign up to set email alerts
|

Novel Filler-Filled-Type Polymer Electrolyte Membrane for PEFC Employing Poly(vinylphosphonic acid)-b-polystyrene-Coated Cellulose Nanocrystals as a Filler

Abstract: Low-acidity polymer electrolyte membranes are essential to polymer electrolyte fuel cells (PEFCs) and water electrolysis systems, both of which are expected to be next-generation energy and hydrogen sources. We developed a new type of highperformance polymer electrolyte membrane (PEM) in which the core particles are precisely electrolyte polymer coated and filled into binder resin. Cellulose nanocrystals (CNCs), which have attracted attention as light, rigid, and sustainable materials, were selected as the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…It was confirmed that direct current (DC) power was generated at room temperature under atmospheric conditions, indicating that the PEM was of a level that could be put to practical use. In contrast to existing PEM, such as Nafion, which as a result of having superstrong acidity (p K a ∼ −6) by perfluorinated sulfonyl acid needs to use platinum for the catalyst and treat the acid durability around the system, the fabricated membranes have low acidity (p K a ∼ 2.5) and, thus, have the potential to generate electricity using catalysts other than platinum . However, their proton conductivity was still about 1 order of magnitude lower than that of Nafion.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…It was confirmed that direct current (DC) power was generated at room temperature under atmospheric conditions, indicating that the PEM was of a level that could be put to practical use. In contrast to existing PEM, such as Nafion, which as a result of having superstrong acidity (p K a ∼ −6) by perfluorinated sulfonyl acid needs to use platinum for the catalyst and treat the acid durability around the system, the fabricated membranes have low acidity (p K a ∼ 2.5) and, thus, have the potential to generate electricity using catalysts other than platinum . However, their proton conductivity was still about 1 order of magnitude lower than that of Nafion.…”
Section: Introductionmentioning
confidence: 94%
“…The functionalized filler (CNC@PVPA-b-PS) was synthesized using the same fabrication methods used in previous experiments. 22 Obtained CNC@PVPA-b-PS (0.50 g) was dispersed in haloalkane, a highly polar solvent [10:1 mixture of dichloromethane (FUJIFILM Wako Pure Chemical Corporation)/1,2-dichloroethane (FUJIFILM Wako Pure Chemical Corporation)], used to dissolve the binder resins. Simultaneously, each binder resin was dissolved in the same mixture to make the resin solution.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we also tried to fabricate silica@PVPA/PC membranes, however, the affinity between silica@PVPA and PC was too low to produce a freestanding membrane. 28…”
Section: Fabrication Of Silica@pvpa-b-ps/pc Membranementioning
confidence: 99%
“…The PAFC is one of the most popular commercialized FC technologies among the several types of FCs [14,[38][39][40]. Because of their mild working temperature, PAFCs have a long lifespan and a simple build.…”
Section: Types Of Fcsmentioning
confidence: 99%